The incidence of thyroid cancer in focal hypermetabolic thyroid lesions: an 18F-FDG PET/CT study in more than 6000 patients. Issue 12 (December 2016) - Barrio, Martin; Czernin, Johannes; Yeh, Michael W.; Palma Diaz, Miguel F.; Gupta, Pawan; Allen-Auerbach, Martin; Schiepers, Christiaan; Herrmann, Ken
Abstract : Background: The clinical significance of incidental thyroid abnormalities discovered in fluorine-18 fluorodeoxyglucose ( 18 F-FDG) PET/computed tomography (CT) (FDG PET/CT) studies remains controversial. The aim of this large retrospective study was to (a) determine the prevalence of focal 18 F-FDG thyroid uptake on whole-body 18 F-FDG PET/CT studies carried out for nonthyroid cancers and (b) to test whether intense focal 18 F-FDG thyroid uptake is associated with malignancy. Materials and methods: A total of 11 921 18 F-FDG PET/CT studies in 6216 patients carried out at our institution between January 2012 and December 2014 were analyzed. We retrospectively reviewed the medical records of these patients. Eight hundred and forty-five/6216 (13.6%) patients had a thyroid incidentaloma on the basis of the clinical 18 F-FDG PET/CT report. One hundred and sixty/845 (18.9%) of these underwent ultrasound and 98 (61.3%) of these underwent a fine-needle aspiration (FNA). Twenty-six of these 98 (26.5%) patients underwent thyroidectomy. Thyroid lesion and background standardized uptake value (SUVs) for each patient were measured upon review of the 18 F-FDG PET/CT study. We measured maximum standardized uptake value (SUVmax ), thyroid to background TL/TBG, thyroid to bloodpool TL/BP and thyroid to liver TL/L ratios in benign and malignant lesions. Receiver operating curves were calculated to determine optimal cut-off values between malignant and benign lesions. Results: Twenty-one of the 98 patients who underwent FNA biopsy or thyroidectomy had malignant disease (21.4%). Malignant lesions had significantly higher thyroid lesion SUVmax, TL/TBG, TL/BP, and TL/L than benign nodules. The receiver operating curves derived cut-off ratio TL/TBG of more than 2.0 differentiated benign from malignant lesions best with a specificity and sensitivity of 0.76 and 0.88, respectively. Conclusion: The incidence of malignancy in biopsied focal hypermetabolic thyroid lesions is 21.4%. Lesions on 18 F-FDG PET/CT studies, with a ratio TL/TBG more than 2.0, warrant further work-up with ultrasound and FNA to exclude malignancy. Abstract : Supplemental Digital Content is available in the text.